PERAN AL WARAQ DALAM INDUSRI PENERBITAN BUKU ISLAM DAN DAMPAKNYA TERHADAP PERKEMBANGAN KEILMUAN ISLAM - Budhi Santoso (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2019)
Introduction. This article discusses intellectual development in the Islamic world and the role of al-Waraq in the Islamic book publishing industry. Data Collection Method. The method used in this article is the literature study method used in obtaining data. Analysis Data. The data obtained is then grouped according to relevance to the formulation of the problem Results and Discussions. The copying of scientific texts is very instrumental in the spread of knowledge, besides being a copyist of the Al Warraq manuscript, it also acts as editor and publisher of books. that. With the existence of this catalog, we can find out the number of publications at the time and as literature for the study of Muslim works in the golden era. Copyright licenses are issued to avoid plagiarism or recognition of a work by Al Warraq. The Al Warraq profession was slowly displaced by the discovery of printing technology in the fifteenth century. Keyword: al warraq, Islamic scientific development, Islamic Book Publishing Indusrial